Motility Profile of Captive-Bred Marmosets Revealed by a Long-Term In-Cage Monitoring System - Koizumi, Masashi; Nogami, Naotake; Owari, Kensuke; Kawanobe, Akiyo; Nakatani, Terumi; Seki, Kazuhiko (Frontiers in Systems Neuroscience, 2021)
A quantitative evaluation of motility is crucial for studies employing experimental animals. Here, we describe the development of an in-cage motility monitoring method for new world monkeys using off-the-shelf components, and demonstrate its capability for long-term operation (e.g., a year). Based on this novel system, we characterized the motility of the common marmoset over different time scales (seconds, hours, days, and weeks). Monitoring of seven young animals belonging to two different age groups (sub-adult and young-adult) over a 231-day period revealed: 1) strictly diurnal activity (97.3% of movement during daytime), 2) short-cycle (~20 s) transition in activity, and 3) bimodal diurnal activity including a “siesta” break. Additionally, while the mean duration of short-cycle activity, net daily activity, and diurnal activity changed over the course of development, 24-h periodicity remained constant. Finally, the method allowed for detection of progressive motility deterioration in a transgenic marmoset. Motility measurement offers a convenient way to characterize developmental and pathological changes in animals, as well as an economical and labor-free means for long-term evaluation in a wide range of basic and translational studies.